2020
DOI: 10.1016/j.nicl.2020.102492
|View full text |Cite
|
Sign up to set email alerts
|

Reward processing electrophysiology in schizophrenia: Effects of age and illness phase

Abstract: Highlights Schizophrenia patients have intact reward anticipation and early stage reward outcome processing. However, for patients early in their illness course, deficits were evident during late stage reward outcome processing. Patients with schizophrenia who have an older neural brain age have worse depressive symptoms.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…Thus, there appear to be deficits in the sustained processing of unpleasant stimuli in psychosis, and potentially to a lesser extent for pleasant stimuli, which may reflect a deficit in underlying motivational systems that naturally direct and sustain attention to threatening and/or appetitive environmental cues. Indeed, abnormal LPP amplitude in response to reward outcome processing (e.g., wins vs. losses) has been observed in patients with schizophrenia (Abram et al, 2020). Notably, the neural regions involved in purportedly generating the LPP (e.g., amygdala, prefrontal cortex, insula; Hajcak & Foti, 2020; Liu et al, 2012; Sabatinelli et al, 2007, 2013) overlap heavily with neural regions that are consistently found to exhibit reduced activity in patients with psychosis using similar paradigms (Anticevic et al, 2012; Taylor et al, 2012).…”
Section: Emotion Processing Impairment In Psychosismentioning
confidence: 99%
“…Thus, there appear to be deficits in the sustained processing of unpleasant stimuli in psychosis, and potentially to a lesser extent for pleasant stimuli, which may reflect a deficit in underlying motivational systems that naturally direct and sustain attention to threatening and/or appetitive environmental cues. Indeed, abnormal LPP amplitude in response to reward outcome processing (e.g., wins vs. losses) has been observed in patients with schizophrenia (Abram et al, 2020). Notably, the neural regions involved in purportedly generating the LPP (e.g., amygdala, prefrontal cortex, insula; Hajcak & Foti, 2020; Liu et al, 2012; Sabatinelli et al, 2007, 2013) overlap heavily with neural regions that are consistently found to exhibit reduced activity in patients with psychosis using similar paradigms (Anticevic et al, 2012; Taylor et al, 2012).…”
Section: Emotion Processing Impairment In Psychosismentioning
confidence: 99%
“…23,24 Increasing evidence suggests that SCH may not be able to use prospective rewards to modulate subsequent targeted behavior due to dopaminergic transmission disturbances in the frontostriatal regions. 25 Yet, recent studies did not demonstrate the alteration of reward-related P300 in patients, 17,26 despite the existence of an association between P300 and negative symptoms in patients. 27,28 The monetary incentive delay (MID) task is an effective experimental paradigm to evaluate neural activity which includes reward and loss anticipation and outcome 29 in SCH.…”
Section: Introductionmentioning
confidence: 97%
“…While the responses to those cues in the reward condition maximize gains, they minimize the losses in the punishment condition. 26,31 Recent advances in understanding the motivational impairments in schizophrenia in the field of neuroscience offer a promising area. 32 Nevertheless, there is still a lack of studies searching for the neural correlates of anticipatory and consummatory facets of anhedonia in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations